Revenge Porn: a Critical Content Analysis of the Nation’s Laws and Reflection upon Social Science Research - Fallik, Seth W. (Criminology, criminal justice, law & society, 2022)
Though revenge porn is a relatively new phenomenon in popular culture, the first instance can be dated back as early as the 1950s. Despite its nearly 70-year existence, very little is known about this crime or how it is expressed in criminal justice legislation. To further examine the former, the present study analyzes the legislation surrounding revenge porn and reflects upon the scant social science research through a content analysis of the nation’s state statutes. Though innovative revenge porn laws were observed, much of this legislation appeared inconsistent with how this crime is perpetrated and is best described as vague and medley. In light of these observations, policy implications and areas of future research are discussed.